Molecular genetic study of selected ribosomal protein genes in nasopharyngeal carcinoma cases. - Ma, Xiang Ru (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Nasopharyngeal carcinoma (NPC) is a cancer of the head and neck that is highly associated with Epstein - Barr virus (EBV) infection and shows strong ethnic and geographical clustering. In Malaysia, NPC is the fourth most common cancer on overall and the third most common cancer among males. The disease is often diagnosed at relatively later stages due to the signs and symptoms that are not obvious and which could often be mistaken as common illness. It is thus important to identify the molecular pathway(s) and genes involved in NPC carcinogenesis in order to have better prognosis of the disease. Ribosomal protein (RP) genes have recently been implicated in many human disorders and diseases. Apart from their roles in the canonical protein biosynthesis pathway, studies have shown that RP genes could also have extra ribosomal functions. Herein, the potential involvements and role(s) of nine selected ribosomal protein (RP) genes were examined at transcript level in NPC-derived cell lines and paired biopsies using real-time PCR, microarray and DNA sequencing techniques. Westernblotting was performed on NPC-derived cell lines to study the expression of RPs at protein level. Student’s- t test, correlation test and multiple linear regression test were used to determine the statistical significance of result obtained. Both RPS15 and L14 were underexpressed at transcript level in cases of NPC whereas RPS3, S7, S15, S26, S27, L32 and L34 were not differentially expressed. Protein-protein dock models built via bioinformatics approach showed potential interactions between RPS15 with the Agenet-like motif 1 of FMRP. This motif is located in the NDF domain that has been reported to be involved in protein-RNA and protein-protein interactions. No nucleotide aberrancy was detected in the coding regions of all nine RPs examined. There was no association established between the expression of each RP with p53, as well as with NPC related clinicopathologic factors studied.p53 which normally acts as the genome guardian of cells was also not differentially expressed at transcript and protein levels; and no mutation was detected in its entire coding region. Current findings suggested possible involvement of RPS15 and L14 in NPC pathogenesis. RPS15 protein could possibly regulate translation by interacting with FMRP – a predicted function that warrants further experimental investigation. Evidence showed that RPS3, S7, S15, S26, S27, L32 and L34 were unlikely to be directly involved in NPC pathogenesis. All these further strengthen the view that NPC is a unique and distinct type of head and neck cancers.